Gross Alpha Activity Concentration in Water Sample of Old Dhaka, Bangladesh by Zinc Sulphide Scintillation Detector (Dhaka University Journal of Applied Science and Engineering, 2022)
ZnS(Ag) was used to measure the gross alpha activity in drinking water of Old Dhaka, Dhaka District, Bangladesh. Screening was carried out for collected twenty samples; of which ten were tap water, five were ground water and the rest of five were bottled water samples. The gross alpha activity concentration was ranged from 0.84 + 0.06 to 14.40 + 0.23 mBq/L with an average activity of 6.52 + 0.18 mBq/L for tap water samples. For ground water samples, the gross alpha activity concentration was ranged from 0.87 + 0.18 to 1.46 + 0.48 mBq/L with an average activity of 1.22+ 0.63 mBq/L. The gross alpha activity concentrations were ranged from 5.07 +0.30 to 24.70 + 0.69 mBq/L with an average activity of 13.89 + 0.45 mBq/L for bottled water samples. The gross alpha activities for all cases were found below than the recommended value of 0.5 Bq/L or 500 mBq/L given by World Health Organization (WHO) in 2004. The annual effective doses for all cases were found below than the recommended value of 0.1 mSv/year given by International Commission on Radiological Protection (ICRP).DUJASE Vol. 6 (2) 77-81, 2021 (July)